THE EFFECTIVENESS OF THE CENTER FOR PLANT VARIETY PROTECTION AND AGRICULTURAL LICENSING IN PROVIDING LEGAL PROTECTION OF PLANT VARIETIES - Effendi, Indah Syalsabilla; Nurwati, Nurwati; Ilyanawati, R. Yuniar Anisa (Department of Transnational Business Law, Faculty of Law Universitas Padjadjaran, 2023)
ABSTRACTThe development of the agricultural sector is one of the urgencies of the country's development, the large variety of potential natural resources from germplasm produces various types of agricultural products that have been improved in quality. With researchers and modern technology helping plant breeders in producing new superior varieties of plants. Indonesia's participation with the International Convention for the Protection of New Varieties of Plants (UPOV Convention) makes the reason for the need for Indonesia to protect the creation of new varieties of plants by law so that the formation of an institution engaged in the Protection of Plant Varieties which then must be seen its effectiveness. The purpose of this study is to determine and analyze the role of related institutions in providing legal protection for plant varieties. The method in this research is carried out with empirical juridical research methods, namely carried out with a statutory approach as well as conducting interviews at related institutions. The results obtained through this research that there are still obstacles in the protection of plant varieties, namely that there are still many people or farmers who have not been educated so that there are practices of violations committed and although there are many violations, not many cases have been reported because it is considered that there is no definite form of protection for plant breeders when a violation occurs. Of course, all protection provided depends on regulations. So it is suggested that in addition to intensively conducting socialization, the government can reopen related regulations and make adjustments through the renewal of these regulations.